The age and residence impact on IgE serum level in patients with allergic asthma - Raghdah Maytham Hameed; Huda Hadi Al-Hasnawy; Haidar Abdul Amir Najim Abood (Medical Journal of Babylon)
Abstract Background: Immunoglobulin E (IgE) has a role in mediating allergic reactions and their powerful effector functions, but numerous factors influence its value. Objective: To find any difference in total and specific IgE serum levels at the different age groups and residences. Materials and Methods: Eighty-seven asthmatic children, including 57 males and 30 females with asthma aged between 1 and 16 years old, 32.2% living in rural and 67.8% living in urban, were collected at Kerbala Teaching Hospital for Children. All asthmatic children in this study were subjected to measuring total IgE level using AccuBind IgE ELISA kit, Human Chlamydia pneumoniae IgG using Cpn IgG ELISA kit, and Human C. pneumoniae IgE using Cpn IgE ELISA kit. Results: There was a significant positive linear correlation between age and total IgE level and a significant negative correlation between age and C. pneumoniae IgE in asthmatic children (0.255, P = 0.017, -0.233, P = 0.03, respectively). Further, there was a significant positive linear correlation between total IgE and C. pneumoniae IgE under age controlling (0.225, P = 0.019). In urban residents, the asthmatic children more than eleven years old had a low C. pneumonia IgE serum level (5.845 ± 1.821 ng/L) compared with asthmatic children who lived in rural areas (8.206 ± 2.793 ng/L). Depending on age groups, there was a significant difference (P = 0.047) in C. pneumonia IgE serum levels in asthmatic children who lived in urban areas. Conclusion: C. pneumonia-specific IgE decreased in early adulthood urban asthmatic children.